Increased Right Frontal Brain Activity During the Mandarin Hearing-in-Noise Test - Song, Fengxiang; Zhan, Yi; Ford, James C.; Cai, Dan-Chao; Fellows, Abigail M.; Shan, Fei; Song, Pengrui; Chen, Guochao; Soli, Sigfrid D.; Shi, Yuxin; Buckey, Jay C. (Frontiers in Neuroscience, 2020)
Purpose: Previous studies have revealed increased frontal brain activation during speech comprehension in background noise. Few, however, used tonal languages. The normal pattern of brain activation during a challenging speech-in-nose task using a tonal language remains unclear. The Mandarin Hearing-in-Noise Test (HINT) is a well-established test for assessing the ability to interpret speech in background noise. The current study used Mandarin HINT (MHINT) sentences and functional magnetic resonance imaging (fMRI) to assess brain activation with MHINT sentences. Methods: Thirty native Mandarin-speaking subjects with normal peripheral hearing were recruited. Functional MRI (fMRI) was performed while subjects were presented either HINT “clear” sentences with low-level background noise (signal-to-noise ratio [SNR] = +3 dB) or “noisy” sentences with high-level background noise (SNR = –5 dB). Subjects were instructed to answer with a button press whether a visually presented target word was included in the sentence. Brain activation between noisy and clear sentences was compared. Activation in each condition was also compared to a resting, no sentence presentation, condition. Results: Noisy sentence comprehension showed increased activity in areas associated with tone processing and working memory, including the right superior and middle frontal gyri (Brodmann Areas [BAs] 46, 10). Reduced activity with noisy sentences was seen in auditory, language, memory and somatosensory areas, including the bilateral superior and middle temporal gyri, left Heschl’s gyrus (BAs 21, 22), right temporal pole (BA 38), bilateral amygdala-hippocampus junction, and parahippocampal gyrus (BAs 28, 35), left inferior parietal lobule extending to left postcentral gyrus (BAs 2, 40), and left putamen. Conclusions: Increased frontal activation in the right hemisphere occurred when comprehending noisy spoken sentences in Mandarin. Compared to studies using non-tonal languages, this activation was strongly right-sided and involved subregions not previously reported. These findings may reflect additional effort in lexical tone perception in this tonal language. Additionally, this continuous fMRI protocol may offer a time-efficient way to assess group differences in brain activation with a challenging speech-in-noise task.